General approach to the problem of disruption forces in tokamaks. (8th October 2015) - Pustovitov, V.D.
Abstract: An approach for calculating the force on the vessel wall during plasma disruptions in tokamaks is proposed. It is mainly based on the Maxwell equations and, therefore, is general. Another essential element is the integral force balance on the plasma that strongly constrains the possible solutions. The derived expressions are valid at any disruption scenario and finally give the net forces in terms of the magnetic perturbations behind the wall. The result can be used with magnetic measurements alone. It shows that the geometrical inhomogeneity of the wall and its resistivity are the key factors determining the direction and amplitude of the force.